2012
DOI: 10.1002/pmic.201200209
|View full text |Cite
|
Sign up to set email alerts
|

The15N isotope effect inEscherichia coli: A neutron can make the difference

Abstract: Several techniques based on stable isotope labeling are used for quantitative MS. These include stable isotope metabolic labeling methods for cells in culture as well as live organisms with the assumption that the stable isotope has no effect on the proteome. Here, we investigate the (15) N isotope effect on Escherichia coli cultures that were grown in either unlabeled ((14) N) or (15) N-labeled media by LC-ESI-MS/MS-based relative protein quantification. Consistent protein expression level differences and alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 45 publications
3
53
0
Order By: Relevance
“…Preliminary experiments showed that the growth rate of E. coli is retarded at a significant enrichment of 15 N, which is in line with literature data12. For instance, at 50% enrichment, the lag time was extended by 0.53%, the growth rate decreased by 0.77%, and the maximum density was reduced by 0.94% (Figure S1).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Preliminary experiments showed that the growth rate of E. coli is retarded at a significant enrichment of 15 N, which is in line with literature data12. For instance, at 50% enrichment, the lag time was extended by 0.53%, the growth rate decreased by 0.77%, and the maximum density was reduced by 0.94% (Figure S1).…”
Section: Resultssupporting
confidence: 89%
“…The heavy isotopes of C, N and O are currently considered “safe”10, although recently Turck et al have reported that mice growth on 15 N diet exhibit systematic behavioural differences11. They also found that E. Coli grow slower in a media highly enriched with 15 N12. These examples demonstrate that the effects of heavy isotopic substitution on biology are still insufficiently understood13.…”
mentioning
confidence: 99%
“…They also found that the growth of the bacterium Escherichia coli ( E . coli ) is slowed down in a media highly enriched with 15 N[8]. …”
Section: Introductionmentioning
confidence: 99%
“…Heavier isotopes form stronger bonds that require higher energy to break them, which ultimately slows down the chemical reaction rate910. Slower reactions for organisms, in the context of isotopic labeling, can result in changing metabolic fluxes11 and decreased growth and development712. A few studies have addressed effects of externally supplied heavy isotopes on the growth and morphology of algae.…”
mentioning
confidence: 99%